Biologija celice: Navodila za vaje za študijski program Biologija - Dariš, Barbara; Lipovšek, Saška (University of Maribor Press, 2021)
Cell Biology: Laboratory Work for the Study Program Biology. Laboratory work for students of biology contains eight chapters of major topics from the field of cell biology (structure and function of the cell).